Effect of hyoscine butylbromide on cervical dilation during labor - Treviño Salinas, Emilio Modesto; Castillo Martín del Campo, G. E.; Ayuzo del Valle, Cipatli; Guzmán López, Abel; Soria López, Juan Antonio; Iglesias Benavides, José Luis; Ambriz López, Roberto (UANL. Facultad de Medicina, 2015)
To compare the effects of intravenous hyoscine butylbromide versus placebo on the duration of labor in term pregnancies. Materials and methods: 86 patients were selected and randomly assigned to receive intravenous hyoscine butylbromide (20 mg twice) (n = 43) or an intravenous placebo (saline solution 10 cc) (n = 43). We evaluated maternal adverse effects, effects on neonatal Apgar score, cervical dilatation 1 h after drug administration and the interval between the onset of labor and delivery. Results: No significant differences were observed in the duration of phases of labor between the two groups. No significant differences were found between the groups in Apgar scores at 1 and 5 min. No maternal adverse effects were observed or reported due to the use of hyoscine butylbromide or the placebo. On the first phase of primigravidas it shortens the first labor phase up to 159.1 ± 84 min vs. the control group (p = 0.002). Conclusion: Hyoscine butylbromide oxytocin shortens the duration of labor in term primigravida pregnancies. No side effects were reported.